2016
DOI: 10.3389/fimmu.2016.00637
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of IgT and IgM upon Parasitic, Bacterial, Viral, and Dietary Challenges in a Perciform Fish

Abstract: Three different immunoglobulin (Ig) isotypes can be found in teleost fish, IgM, IgD, and the teleost-specific IgT. IgM is considered to have a systemic activity, and IgT is attributed a mucosal role, similar to mammalian IgA. In this study, the complete sequence of gilthead sea bream IgM and IgT in their membrane (m) and soluble (s) forms are described for the first time in a perciform fish. Their constitutive gene expression is analyzed in different tissues, and their regulation upon viral, bacterial, parasit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
82
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 62 publications
7
82
1
2
Order By: Relevance
“…Interestingly, despite the higher parasite prevalence at the posterior intestine in T1, there was a slower progression of the infection along the intestinal tract than in T2, which could be due to the higher levels of specific antibodies observed at high temperatures. Previous studies have described the important role of IgM in E. leei ‐GSB infections, with an overexpression of IgM in posterior intestine and head kidney in infected GSB (Piazzon et al, ). Another study showed that GSB that survived an infection with E. leei showed high levels of parasite‐specific IgM in serum, even several months after eliminating the parasite (Picard‐Sánchez et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, despite the higher parasite prevalence at the posterior intestine in T1, there was a slower progression of the infection along the intestinal tract than in T2, which could be due to the higher levels of specific antibodies observed at high temperatures. Previous studies have described the important role of IgM in E. leei ‐GSB infections, with an overexpression of IgM in posterior intestine and head kidney in infected GSB (Piazzon et al, ). Another study showed that GSB that survived an infection with E. leei showed high levels of parasite‐specific IgM in serum, even several months after eliminating the parasite (Picard‐Sánchez et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…However, carnivorous fish fed with little or no fish meal/fish oil diets have been shown to have a wide range of metabolic effects that, in addition to affecting growth performance, can also impact on health (Martin & Król, ; Torrecillas et al., ) or the nutritious value of seafood products as the most important source of omega‐3 in the human diet (Ballester‐Lozano, Benedito‐Palos, Mingarro, Navarro, & Pérez‐Sánchez, ; Ballester‐Lozano et al., ; Benedito‐Palos et al., ). The precise mechanisms for this disruption of fish health and welfare are not fully understood, although recent studies with extreme diet formulations pointed out in gilthead sea bream that dietary supplementation of plant‐based diets with sodium butyrate helps to prevent in long‐term feeding trials the inflammation of the intestinal epithelium, preserves the integrity of the intestinal barrier (Estensoro et al., ) and improves bacteria and parasite disease outcomes (Piazzon et al., , ). Samples from these fish within the ARRAINA project and previous Atlantic salmon and gilthead sea bream from AQUAMAX trials have been used to assess the impact of the combined and maximized replacement of marine feed sources by plant ingredients on the feed‐to‐fillet transfer of contaminants (Table shows the ingredients and chemical composition of aquafeeds).…”
Section: Plant‐based Diets Experimental Set‐up and Data Collectionmentioning
confidence: 99%
“…However, high inclusion levels of plant-ingredients are often related with a pro-inflammatory condition with a negative impact on fish health and stress resilience [7][8][9][10]. Plant-based diets can also alter the normal sex proportion ratio, enhancing the male-female reversal in the protandric gilthead sea bream as the result of less powerful functional females during the reproduction period [11].…”
Section: Introductionmentioning
confidence: 99%